The Impact of Personal Computer on Students’ Academic Performance - Blah, Sadat (Advances in Social Sciences Research Journal, 2021)
ABSTRACT This study aimed to determine the effects of Personal Computer on students' academic performance of the Grade 11 Senior High School students at MSU-Maguindanao. Specifically, this study identified the uses of Personal Computers as rated by the students in their studies, the academic performance of respondents with Personal Computer, the academic performance of respondents without Personal Computer, and the significant difference in academic performance of respondents with and without Personal Computer. Survey questionnaire was used as an instrument in gathering data. The questionnaire contains ten (10) related to the uses of computer in the students’ studies. The 10 questions are measured in terms of a 4- point scale such as: 1 for always, 2 for often, 3 for seldom and 4 for never. The statistical tools used in the analysis of data are the frequency count and the mean to describe the effects of personal computer on Senior High School students’ academic performance. The data gathered were consolidated and tabulated. The computations were done manually with the aid of scientific calculator. Findings show that the academic performance of the students with personal computer is generally higher than those without personal computer. Therefore, personal computer has effects in improving the students' academic performance. Keywords: Impact, Personal Computer, Students’ Academic Performance